Adolescents' self-concept in terms of their parents' marriage - Ruwaedah, St; Puspita Dewi, Eva Meizara (Polteknik Ilmu Pemasyarakatan, 2023)
Parental divorce can influence the way teenagers recognize themselves in forming one of their developmental tasks, namely self-concept. Adolescents with different family statuses, divorced and non-divorced, may have different views and expectations regarding themselves. The aim of this research is to determine the differences in self-concept of adolescents with divorced and non-divorced parents. A total of 106 students of SMAN 7 Makassar with an age range of 14-18 years were selected using Accidental Sampling. The measuring instrument used is the self-concept scale. The hypothesis is explained using the Mann Whitney test using SPSS 16 for Windows. The results of the study showed that there was a difference between the self-concept of adolescents with divorced parents and adolescents with non-divorced parents (p=0.00 <0.05). Adolescents with divorced parents have a mean rank of 63.42 and adolescents with non-divorced parents have a mean rank of 42.58, so it is concluded that adolescents with divorced parents have high self-concept scores.